«Noget af et eksperiment» : Harald Schwenzens stumfilmadaptasjon (1922) av Knut Hamsuns roman Pan (1894) - Wærp, Lisbeth Pettersen (Nordlit, 2020)
Hamsun’s novel is composed as short state- and mood-oriented chapters, contains two contrasting first person narrators, four different time levels, and displays an emphasis on memory, dream, the unconscious and the irrational. The characters, especially the protagonists Glahn and Edvarda, appear to lack clear motives, and the plot composition is vague and open. Such a composition is challenging to adapt into a film, and differs greatly from both the artistic conventions in contemporary Norwegian peasant and rural films, and from the emerging Hollywood style and what would eventually become the classic film narrative. The main questions asked in this article are how these challenges are solved, what characterizes Schwenzen’s film as an adaptation of Hamsun’s novel, and how the adaptation relates to Norwegian film history and to the history of the novel’s reception and interpretation. An important point in the article is that the adaptation adopts the novel’s modernist narrative and form, and that the melodramatic means of the silent film reinforce crucial innovative modernist aspects adopted from the novel.